Effective family–school communication for students with learning disabilities: Associations with parental involvement at home and in school. (September 2019) - Yotyodying, Sittipan; Wild, Elke
Highlights: Parents of students with LD score high on effective family–school communication. Effective family–school communication appears to enhance parental involvement. Crucial barriers are parental SES and parental perceived social exclusion.